PERCOBAAN PEMBUATAN FASA INTERMETALIK Nb3Sn DENGAN PROSES SINTERING LOGAM NIOBIUM (Nb) DAN TIMAH (Sn) - Firdiyono, Florentinus; Pramono, Andika Widya; Sebleku, Pius; Ciptasari, Nurhayati Indah; Suryantoro, Anton (Jurnal Metalurgi, 2011)
Determination of optimum conditions include milling time of Nb and Sn with HEM, ratio of Nb and Sn, heating time and heating temperature of mixed Nb and Sn. Characterization of Nb3Sn produced from the process was performed using DTA, XRD, SEM and EDS. The results of SEM and XRD analysis showed the minimum time needed for milling Nb and Sn are 3 hours, and the result of DTA analysis showed the intermetalic phase of Nb3Sn was occured at the temparetuir around 700 °C. The result of XRD analysis for mixed Nb and Sn showed that by the increasing of heating time will produced more intermetalic phase of Nb3Sn.